PERANAN PROTOTIPE DALAM PENDEFINISIAN KONSEP ABSTRAK â MARAHâ DAN âBENCIâ - Sukyadi, Didi (Universitas Muhammadiyah Surakarta, 2006)
In Indonesian Great Dictionary, both of the words âangryâ and âhateâ are more or less defined as something uneasy. This definition has actually aroused over- whelming question for in daily use the two words seem to be different. How differ- ent they are can be answered by using the reference of prototype theory which will be applied on the abstract concept for the characteristics of the two words. In this study, the respondents are 42 students of the eight semester of English Depart- ment, UPI. They are presented with open questions to identify the kinds of proto- type and its cognitive model. In addition, they are expected to evaluate the best attribute for the words angry and hate. The result shows that the word âangryâ can be physiologically and psychologically identified, while another word, âhateâ can only be psychologically identified. Moreover, there is family relateness in their cognitive model. This fact influences the implicit meaning of the two words in the current dictionary.Â Key words: prototype theory, cognitive model, dan konsep abstrak.